Self-Compassion and Body Image: Efforts to Build Self-Acceptance Among Students - Zahra, Dinda Az; Syarif Hidayatulloh, Yasin (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Negative body image has become increasingly prevalent among young adults, particularly university students, due to exposure to social media and societal beauty standards. Self-compassion is considered a protective factor that enhances self-acceptance and improves body perception. This study aimed to examine the effect of self-compassion on body image among psychology students in Yogyakarta. A quantitative correlational design was employed with a total sample of 102 students selected using purposive sampling. Data were collected using the Self-Compassion Scale (Neff, 2003) and the Body Image Scale (Cash & Pruzinsky, 2002). Data analysis included Kolmogorov–Smirnov normality testing, linearity testing, and Pearson Product Moment correlation using SPSS 26. The results revealed a positive and significant relationship between self-compassion and body image (r = 0.310; p = 0.002). The findings indicate that higher levels of self-compassion are associated with more positive body image among students. These results highlight the role of self-compassion as a protective factor in fostering healthy body image in the context of social pressures. The study recommends self-compassion-based interventions as a preventive strategy to enhance psychological well-being and promote a healthier body image among young adultsFenomena body image negatif semakin meningkat di kalangan dewasa awal, terutama mahasiswa, akibat paparan media sosial dan tekanan standar kecantikan. Self-compassion dipandang sebagai faktor protektif yang dapat meningkatkan penerimaan diri dan memperbaiki persepsi tubuh. Penelitian ini bertujuan untuk mengetahui pengaruh self-compassion terhadap body image pada mahasiswa Program Studi Psikologi di Yogyakarta. Penelitian menggunakan pendekatan kuantitatif dengan rancangan korelasional. Sampel penelitian berjumlah 102 mahasiswa yang dipilih melalui teknik purposive sampling. Instrumen pengumpulan data berupa skala Self-Compassion Neff (2003) dan skala Body Image Cash & Pruzinsky (2002). Analisis data dilakukan menggunakan uji normalitas Kolmogorov-Smirnov, uji linearitas, dan uji korelasi Pearson Product Moment dengan bantuan SPSS 26. Hasil penelitian menunjukkan adanya hubungan positif dan signifikan antara self-compassion dan body image (r = 0,310; p = 0,002). Semakin tinggi self-compassion yang dimiliki mahasiswa, semakin positif pula citra tubuh mereka. Temuan ini mengindikasikan bahwa self-compassion berperan sebagai faktor protektif yang dapat memperkuat citra tubuh positif pada mahasiswa di tengah tekanan sosial. Penelitian ini merekomendasikan intervensi berbasis self-compassion sebagai upaya preventif untuk meningkatkan kesejahteraan psikologis dan membangun body image yang sehat pada generasi muda